2018
DOI: 10.5935/2595-0118.20180055
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and chronic pain in institutionalized elderly women

Abstract: BACKGROUND AND OBJECTIVES: Sarcopenia and chronic pain are geriatric syndromes that negatively impact the lives of the affected elderly, their families and the routine of health services, as is the case of long-term care institutions for the elderly. The objective of this study was to verify the relationship between sarcopenia and chronic pain in institutionalized elderly women. METHODS: A cross-sectional, population-based study was carried out in 24 long-term care institutions for the elderly, in Passo Fundo/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
1
3
0
8
Order By: Relevance
“…Still, there was no relationship between the HGS and chronic pain, but between the HGS and the factors gender and age. In this study, it was found that the profile of the institutionalized elderly consisted predominantly of private residents of LTCF, women, long-lived, widows and with education from 1 to 8 years 12 and that are in agreement with other studies 11,17,18 . With the considerable increase in the number of elderly people in recent times, musculoskeletal disorders, especially chronic pain, have been one of the main complaints among this population 19 , and in up to 80% of cases, these symptoms persist for at least two years until the search for treatment 20 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Still, there was no relationship between the HGS and chronic pain, but between the HGS and the factors gender and age. In this study, it was found that the profile of the institutionalized elderly consisted predominantly of private residents of LTCF, women, long-lived, widows and with education from 1 to 8 years 12 and that are in agreement with other studies 11,17,18 . With the considerable increase in the number of elderly people in recent times, musculoskeletal disorders, especially chronic pain, have been one of the main complaints among this population 19 , and in up to 80% of cases, these symptoms persist for at least two years until the search for treatment 20 .…”
Section: Discussionsupporting
confidence: 92%
“…As this was a large research, a large team was needed to perform data collection, and several interviewers were required to apply the sociodemographic questionnaire and the manual dynamometry test. To minimize possible biases, they were previously trained and oriented, as explained in the "methods" section in another published study 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…O envelhecimento vem sendo um processo cada vez mais comum na sociedade e até em países subdesenvolvidos já é possível observar uma grande quantidade de indivíduos de terceira idade, sendo que junto a eles aparecem também os problemas relacionados a velhice, que por sua vez podem intervir diretamente na qualidade de vida dos mesmos, no núcleo familiar que se encontram e na saúde pública. 12 A sarcopenia é um dos principais fatores que interfere na qualidade de vida do idoso, por se tratar de um processo de desgaste muscular, no qual o indivíduo perde força, massa e musculatura esquelética, dificultando assim sua mobilidade e com isso acarretando diversos outros problemas. 12 Com a falta de mobilidade e ações físicas cada vez mais restrita, parte dos idosos acabam sendo institucionalizados, já que diante a sociedade e a família podem perder seu valor e até mesmo a sua função.…”
Section: Fatores Que Interferem Na Qualidade De Vida Do Idosounclassified